2004
DOI: 10.1091/mbc.e04-01-0056
|View full text |Cite
|
Sign up to set email alerts
|

Gap Junction Channel Protein Innexin 2 Is Essential for Epithelial Morphogenesis in theDrosophilaEmbryo

Abstract: Direct communication of neighboring cells by gap junction channels is essential for the development of tissues and organs in the body. Whereas vertebrate gap junctions are composed of members of the connexin family of transmembrane proteins, in invertebrates gap junctions consist of Innexin channel proteins. Innexins display very low sequence homology to connexins. In addition, very little is known about their cellular role during developmental processes. In this report, we examined the function and the distri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
103
0
4

Year Published

2005
2005
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(112 citation statements)
references
References 67 publications
5
103
0
4
Order By: Relevance
“…innexin2-GFP cDNA was derived from pUAST-innexin2-GFP, which had been already used for the generation of transgenic flies (Bauer et al 2004). innexin2-Myc was generated by PCR reaction from LD11658 containing the entire innexin2 cDNA using specific innexin2 primer pairs (innexin2 start-primer: 5 -GGAATTCCAAAATGTTTGATGTCT TTGGGT -3 ; innexin2 stop-primer containing the Myc-tag, which is printed in bold letters: 5 -CGCTCGAGCG GTTACAGATCCTCTTCAGAGATGAGTTTC TGCTCGGCGTCGAAGGGCCGCTTG-3 ).…”
Section: Plasmidsmentioning
confidence: 99%
See 3 more Smart Citations
“…innexin2-GFP cDNA was derived from pUAST-innexin2-GFP, which had been already used for the generation of transgenic flies (Bauer et al 2004). innexin2-Myc was generated by PCR reaction from LD11658 containing the entire innexin2 cDNA using specific innexin2 primer pairs (innexin2 start-primer: 5 -GGAATTCCAAAATGTTTGATGTCT TTGGGT -3 ; innexin2 stop-primer containing the Myc-tag, which is printed in bold letters: 5 -CGCTCGAGCG GTTACAGATCCTCTTCAGAGATGAGTTTC TGCTCGGCGTCGAAGGGCCGCTTG-3 ).…”
Section: Plasmidsmentioning
confidence: 99%
“…It has been shown that innexin1 (ogre) and innexin8 (shakingB) are involved in the physiology of the giant fibre and the adult visual systems (Watanabe and Kankel 1990;Curtin et al 2002;Krishnan et al 1993;Phelan et al 1996Phelan et al , 2005Shimohigashi and Meinertzhagen 1998;Zhang et al 1999;Jacobs et al 2000); innexin4 (zero population growth) controls germ cell differentiation (Tazuke et al 2002;Gilboa et al 2003) and we have recently shown that during foregut morphogenesis, innexin2 is a Wingless/WNT target gene that coordinates epithelial morphogenesis . Mutants for innexin2 (kropf), which lack both their maternal and zygotic innexin2 contributions fail to develop any epithelial tissues, and overexpression of innexin2 in the epidermis results in multilayering and irregular cell shapes suggesting that innexin2 is a key factor to control epithelial organization during morphogenesis of tissues and organs in the body (Bauer et al 2004). …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A similar protein family found in fruit flies and nematodes was named innexin (INvertebrate conEXIN) (Phelan et al, 1998a). Some innexin mutants of fruit flies and nematodes are known to show lethal failure during morphogenesis (Starich et al, 2003;Bauer et al, 2004).…”
Section: Introductionmentioning
confidence: 99%